Sunflower waste - manganese iron oxide composite for hazardous dye removal - Uygunoz, Deniz; Demir, Funda; Ozen, Meral Yildirim; Derun, Emek Moroydor (ELSEVIER, 2022)
Sunflower waste (SF), an easily available agricultural waste was used as a primary material in the synthesis of sunflower waste - manganese iron oxide (SF-MIO) composite for the aim of waste recycling and synthesizing new composite material for dye adsorption. The synthesized adsorbent was characterized using various techniques such as Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric and differential thermal analysis (TG-DTA) and Brauner-Emmett-Teller (BET) analysis. Dye adsorption ability of the SF-MIO composite in the aqueous solution was investigated using the anionic dye Congo Red (CR). Effect of adsorption parameters such as adsorbent dosage, temperature, initial dye concentration and time were investigated. According to the characterization results, manganese iron oxide addition provided porous microstructure to sunflower waste and increased its surface area from 1.1814 to 47.1415 m(2)/g thus made sunflower waste more suitable for adsorption. Adsorption process was maintained in endothermic nature and maximum adsorption capacity of SF-MIO on to CR was calculated as 45.66 mg/g. Pseudo-first order, pseudosecond order, Elovich kinetic models and Langmuir, Freundlich, Temkin and Halsey isotherms were studied. The adsorption behavior of CR on SF-MIO composite can be well described by Freundlich and Halsey isotherm models (R-2=0.996) and pseudo-second order kinetic model (R-2=0.999).
Keywords: Sunflower waste; Manganese iron oxide; Dye; Adsorption; CONGO RED-DYE; EQUILIBRIUM; BIOSORPTION; KINETICS; CARBON; Chemistry